2014
DOI: 10.1371/journal.pgen.1004696
|View full text |Cite
|
Sign up to set email alerts
|

Fast Evolution from Precast Bricks: Genomics of Young Freshwater Populations of Threespine Stickleback Gasterosteus aculeatus

Abstract: Adaptation is driven by natural selection; however, many adaptations are caused by weak selection acting over large timescales, complicating its study. Therefore, it is rarely possible to study selection comprehensively in natural environments. The threespine stickleback (Gasterosteus aculeatus) is a well-studied model organism with a short generation time, small genome size, and many genetic and genomic tools available. Within this originally marine species, populations have recurrently adapted to freshwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
231
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(254 citation statements)
references
References 71 publications
17
231
3
Order By: Relevance
“…At present, the feasibility of whole genome resequencing for ecological genomics depends somewhat on genome size and complexity, as well as budget. In ecological genomics of fishes more generally, stickleback fishes (genome size 675 Mb) are now often whole genome resequenced (Jones et al, 2012;Terekhanova et al, 2014) as are some cichlids (genome size *1 Gb) either with few individuals at high coverage (e.g. Brawand et al, 2014) or with individuals pooled and overall lower coverage focusing on fixed differences (e.g.…”
Section: Whole Genome Resequencingmentioning
confidence: 99%
“…At present, the feasibility of whole genome resequencing for ecological genomics depends somewhat on genome size and complexity, as well as budget. In ecological genomics of fishes more generally, stickleback fishes (genome size 675 Mb) are now often whole genome resequenced (Jones et al, 2012;Terekhanova et al, 2014) as are some cichlids (genome size *1 Gb) either with few individuals at high coverage (e.g. Brawand et al, 2014) or with individuals pooled and overall lower coverage focusing on fixed differences (e.g.…”
Section: Whole Genome Resequencingmentioning
confidence: 99%
“…One way in which these regions could exert such pleiotropic effects is by harboring loci that influence the expression of many genes, i.e., eQTL hotspots. However, only one of the trans-eQTL hotspots n (continued) found in this study (Chr12a) overlapped with genomic regions repeatedly found to be associated with marine/freshwater divergence by Hohenlohe et al (2010), Jones et al (2012), or Terekhanova et al (2014. Nevertheless, several studies indicate that adaptation to novel aquatic environments may also involve parts of the genome outside these large target regions (DeFaveri et al 2011;Leinonen et al 2012;Ellis et al 2015;Erickson et al 2016;Ferchaud and Hansen 2016).…”
Section: Discussionmentioning
confidence: 53%
“…Association of eQTL with regions under selection Hohenlohe et al (2010), Jones et al (2012), and Terekhanova et al (2014) documented parallel regions of the genome divergent between marine and freshwater sticklebacks on chromosomes 1, 4 (three regions), 7, 11, and 21. We investigated whether these regions harbored important trans regulators that might contribute to adaptation to different aquatic habitats by comparing the location of these regions with the location of our identified trans-eQTL hotspots.…”
Section: Evaluation Of Eqtl Hotspotsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected histone modification peaks in "divergence islands" regions, which are highly divergent between marine and freshwater populations of sticklebacks 2 . We observed that the majority (17 out of 19) of the islands showed the same chromatin marks (H3K4me1, H3K4me3 and H3K27ac) in fresh water species in their natural salinity (FF) and fresh water species placed into a marine environment (FM).…”
Section: Resultsmentioning
confidence: 99%